PERANAN ICC DALAM PENEGAKAN HUKUM KEJAHATAN GENOSIDA DILIHAT DARI PERSPEKTIF KEADILAN - Yosaliza, Meisyifa; Hazmi, Raju Moh (eScience Humanity Journal, 2024)
Human Rights (HAM) are basic rights inherent in every individual since birth as part of human nature. Human rights are universal, cannot be taken away or violated by anyone, and do not depend on recognition from the state, law, or other individuals. The existence of human rights is very important to protect human dignity and serves as a moral foundation in relations between individuals. In its application, every individual is obliged to respect the human rights of others and understand that every right is accompanied by obligations. Law, which is dynamic, plays an important role in regulating and protecting human rights, although there are challenges in its implementation and fulfillment, such as discrimination, persecution, and arbitrary detention. Other global challenges include armed conflict, humanitarian crises, and information technology and climate change. International Criminal Law and Humanitarian Law have been developed to protect humanity from serious crimes such as genocide, which is recognized as a serious violation of international law. Genocide, defined in the Rome Statute and the Genocide Convention, includes acts intended to destroy a particular group. The International Court of Justice recognizes the prohibition of genocide as a norm of international law that must be complied with. The International Criminal Court (ICC), established by the Rome Statute of 1998, is tasked with trying the crimes of genocide, crimes against humanity, war crimes, and the crime of aggression. The ICC aims to eliminate impunity and achieve global justice, operating when national justice systems are unable to prosecute such crimes. Human rights analysis and theories of state responsibility underscore the importance of international legal protection against the crime of genocide, asserting that states have an obligation to protect the fundamental values of the international community